An annotated checklist of the chondrichthyans of Papua New Guinea - White, William T.; Ko’ou, Alfred (Zootaxa, 2018)
An annotated checklist of the chondrichthyan fishes (sharks, rays, and chimaeras) of Papua New Guinean waters is herein presented. The checklist is the result of a large biodiversity study on the chondrichthyan fauna of Papua New Guinea between 2013 and 2017. The chondrichthyan fauna of Papua New Guinea has historically been very poorly known due to a lack of baseline information and limited deepwater exploration. A total of 131 species, comprising 36 families and 68 genera, were recorded. The most speciose families are the Carcharhinidae with 29 species and the Dasyatidae with 23 species. Verified voucher material from various biological collections around the world are provided, with a total of 687 lots recorded comprising 574 whole specimens, 128 sets of jaws and 21 sawfish rostra. This represents the first detailed, verified checklist of chondrichthyans from Papua New Guinean waters.